KNOWLEDGE MANAGEMENT AND ORGANIZATIONAL CLIMATE INFLUENCE ON LEARNING ORGANIZATION OF THE SOUTHERN BORDER PROVINCES’ PERSONNEL OF PUBLIC UNIVERSITY - Rehlaeba, Muhammadshakir; Phayoonpun, Thammayantee (Journal of MCU Nakhondhat, 2025)
This research aimed to: 1) Study the levels of knowledge management, organizational climate, and the characteristics of being a learning organization among personnel of public universities in the southern border provinces of Thailand, and 2) Examine the influence of knowledge management and organizational climate on the development of learning organizations. The sample consisted of 390 academic and support staff from public universities in the southern border provinces. Stratified sampling was employed. The research instruments comprised three questionnaires: One on knowledge management, one on organizational climate, and one on the characteristics of a learning organization. The reliability coefficients ranged from 0.92 to 0.93. Data were collected through an online questionnaire distributed via Google Forms, with official permission from each institution. The data collection period lasted two months. Descriptive statistics (percentage, frequency, mean, and standard deviation) and inferential statistics (multiple regression analysis) were used for data analysis after confirming the preliminary statistical assumptions. The findings revealed that the levels of knowledge management, organizational climate, and learning organization characteristics among personnel in these universities were at a high level overall and in each aspect. Furthermore, organizational climate had a strong positive influence (β = .603, t = 11.695, p < .001), and knowledge management had a moderate positive influence (β = .292, t = 5.656, p < .001) on the development of learning organizations. Both variables were statistically significant at the .05 level and jointly explained 75.6% of the variance in learning organization characteristics (R² = 0.756, Adjusted R² = 0.755).